Pentingnya Housekeeping bagi Suatu Hotel - Parsidi (Media Wisata, 2004)
The general public tends to think of Housekeeping as the Department that: makes the head, empties the ashtray and waste basked, tidies up the bathroom and leaves fresh towels. The truth of the matter is of course that it takes more manpower to accomplish. Housekeeping's almost countless function than those of any other Department in the lodging industry. Housekeeping's responsibility may begin with fabrics, and progress to the selection and purchase of all furniture and furnishings; it encompasses not only their cleaning but their maintenance, repair, refurbishment and eventual replacement. Areas of concern include: sleeping rooms, meeting rooms, halls and elevator, all considered "front of the house" The designation also includes all other public areas from lobbies to washrooms to restaurant and cocktail lounges. Outdoor areas such as pools and patios. Housekeeping also oversees almost the entire "back of the house", from locker rooms to employee dining, virtually everything.